Quantum mechanical investigation of femtosecond stimulated Raman spectroscopy - Zhao, Bin (2013)
Femtosecond Stimulated Raman Spectroscopy (FSRS) is a novel spectroscopy that offers simultaneous high temporal and spectral resolutions, and it also bears many other advantages, such as fluorescence background free, high signal-to-noise ratio, wide vibrational spectrum range, and rapid data acquisition. The research works in this thesis aim to provide a quantum mechanical investigation on FSRS and try to elucidate the underlying quantum mechanical processes for the first 500 fs photoisomerization dynamics in the excited state of bacteriorhodopsin, and for the side bands with inverse symmetry around the CD stretch frequency of CDCl3 molecule from the direct fifth and cascade processes in time-resolved FSRS. The issue of simultaneous high temporal and spectral resolutions obtained by FSRS is investigated from a quantum mechanical point of view, and the temporal resolution is revealed by the polarization from the inverse Fourier transform of the Stokes line. In the quantum mechanical investigation of the first 500 fs photoisomerization dynamics in the excited state of bacteriorhodopsin, we use four-wave mixing energy level diagrams to describe the FSRS processes, and a 29-mode separable harmonic oscillator model for BR568 in the calculations. From the calculation results, we find that FSRS of BR568 effectively occurs between the ground vibrational state of S1 and high energy vibrational states on BR (S0), and only the ground vibrational state of each of the observed 800-1800 cm−1 modes of S1 is involved in the process. The FSRS dispersive lines are shown to be due to the inverse Raman scattering (IRS) term with |0ih1| vibrational coherence on the S1 surface, and are not due to Raman Initiated by Nonlinear Emission (RINE) with vibrational coherence on the S0 surface. Our calculations show that the RINE process gives rise to broad featureless spectra. We use a quantum mechanical wave packet treatment to investigate the 2D-FSRS of CDCl3 molecule, where a vibrational coherence is initiated with an impulsive Raman pump. It is found that the experimentally observed side bands may come from two processes, which can occur concurrently but with different intensities: a direct fifth-order process taking place on one molecule, and a cascade process comprising two third-order processes on two different molecules. Our quantum mechanical calculation shows that the observed side bands are from the cascade process with stronger intensity, and the appearance of side bands are due to the CARS and CSRS fields produced in the first step of the cascade process. The coherent line shapes of the side bands are correlated with the momentum of the wave packet prepared on the ground state surface by the impulsive pump along the sideband normal coordinate, and the inversion symmetry of the side bands about the C-D stretch frequency is due to the 180◦ phase difference between the CARS and CSRS fields that produced the left and right sidebands. In the elucidation of simultaneous high temporal and spectral resolutions of FSRS, we use both three-state model and wave packet method to investigate FSRS spectra of the vibrational modes with time-dependent frequency. The adiabatic theorem supports the validity of three-state model for the vibrational modes with time-dependent frequency. The wave packet method is more general in treating real initial wave packet and pulses with finite duration. The results obtained by the two methods agree well with each other for offresonance FSRS spectra of the vibrational mode with time-dependent frequency. The high temporal resolution of FSRS is demonstrated by revealing the time-dependent vibrational frequency from the inverse Fourier transform of the Stokes lines. It is also found by the wave packet method that off-resonance FSRS can’t distinguish between coherence and no coherence in the initial wave packet from the line shape and position of the Stokes lines.